The Adjuvant Effects on Vaccine and the Immunomodulatory Mechanisms of Polysaccharides From Traditional Chinese Medicine - Wang, Danyang; Liu, Yonghui; Zhao, Wei (Frontiers in Molecular Biosciences, 2021)
Vaccination is still the most successful strategy to prevent and control the spread of infectious diseases by generating an adequate protective immune response. However, vaccines composed of antigens alone can only stimulate weak immunogenicity to prevent infection in many cases. Adjuvant can enhance the immunogenicity of the antigens. Therefore, adjuvant is urgently needed to strengthen the immune response of the vaccines. An ideal adjuvant should be safe, cheap, biodegradable and biologically inert. In addition to having a long shelf life, it can also promote cellular and humoral immune responses. Traditional Chinese medicine (TCM) has many different ingredients, such as glycosides, polysaccharides, acids, terpenes, polyphenols, flavonoids, alkaloids, and so on. TCM polysaccharides are one of the main types of biologically active substances. They have a large range of pharmacological activities, especially immunomodulatory. TCM polysaccharides can regulate the immune system of animals by binding to multiple receptors on the surface of immune cells and activating different signal pathways. This review focuses on a comprehensive summary of the most recent developments in vaccine adjuvant effects of polysaccharides from many important TCM, such as Artemisia rupestris L., Cistanche deserticola, Pinus massoniana, Chuanminshen violaceum, Astragalus, Ganoderma lucidum, Codonopsis pilosula, Lycium barbarum, Angelica, Epimedium, and Achyranthes bidentata. Moreover, this review also introduces their immunomodulatory effects and the molecular mechanisms of action on animal bodies, which showed that TCM polysaccharides can activate macrophages, the signal pathway of T/B lymphocytes, regulate the signal pathway of natural killer cells, activate the complement system, and so on.